MOTIVASI BERPRESTASI TERHADAP HASIL BELAJAR EKONOMI: ACHIEVEMENT MOTIVATION ON ECONOMIC LEARNING OUTCOMES - Heseziduhu Lase (Pusat Riset dan Inovasi Nasional, 2022)
The purpose of this study was to determine whether there is a relationship between achievement motivation and student learning outcomes. The method used is the correlation method. The research data collection technique used the Liliefors test, regression linearity test, product moment correlation and z test. Based on the results of the Liliefors test, it was stated that the sample was normally distributed, so it was continued with a simple regression test and obtained F_count = 2.21 < F_table = 2.98 so that the X variable to the Y variable was linear. Furthermore, a correlation test was conducted and the value of r_xy=0.944 with r_xy>0 means that there is a positive relationship between achievement motivation and student learning outcomes and is in the very strong category. For the z test (significance test) the results obtained z_count = 5.171 > Z_Table = 1.96 with = 0.05, meaning that there is a positive and significant relationship between achievement motivation and student economic learning outcomes.